2004
DOI: 10.1074/jbc.m311951200
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 Is a Novel RNA-binding Protein

Abstract: The annexins are a family of more than 160 unique annexin proteins that are present in more than 65 different species ranging from fungi and protists to plants and higher vertebrates (1). ANXA2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
112
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 56 publications
6
112
0
Order By: Relevance
“…In addition, antisense oligonucleotides to annexin A2 retard proliferation of Hela cells [24], and the expression of annexin A2 is regulated during the mammalian cell cycle [25]. Recent study has demonstrated ANXA2 is a RNA-binding protein that interacts with the mRNA of the nuclear oncogene, c-myc, and results in an increase in c-Myc protein [26]. Therefore, the up-regulation of ANXA2 may contribute to tumorigenesis of ccRCC through increasing the c-Myc protein level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antisense oligonucleotides to annexin A2 retard proliferation of Hela cells [24], and the expression of annexin A2 is regulated during the mammalian cell cycle [25]. Recent study has demonstrated ANXA2 is a RNA-binding protein that interacts with the mRNA of the nuclear oncogene, c-myc, and results in an increase in c-Myc protein [26]. Therefore, the up-regulation of ANXA2 may contribute to tumorigenesis of ccRCC through increasing the c-Myc protein level.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in cellular ion composition may regulate some of the ion channels such as Atp1a1 and Atp2a1. (d) Annexin A2 has been shown to bind with RNAs (29). Under certain conditions, nuclear annexin A2 was detected (30).…”
Section: Discussionmentioning
confidence: 99%
“…Galectins are well-established carbohydrate-binding proteins (22), but several galectin proteins also localize to the nucleus and exhibit pre-mRNA splicing activity (23)(24)(25). The annexins also form a large protein family, and some members localize to the nucleus and bind RNA (25)(26)(27). Annexin 4 binds to N-glycan (28), and Annexins 4, 5, and 6 bind sulfated glycosaminoglycans (28,29).…”
Section: Discussionmentioning
confidence: 99%